2011
DOI: 10.1016/j.ajhg.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Iron-Sulfur Cluster Scaffold Genes NFU1 and BOLA3 Cause a Fatal Deficiency of Multiple Respiratory Chain and 2-Oxoacid Dehydrogenase Enzymes

Abstract: Severe combined deficiency of the 2-oxoacid dehydrogenases, associated with a defect in lipoate synthesis and accompanied by defects in complexes I, II, and III of the mitochondrial respiratory chain, is a rare autosomal recessive syndrome with no obvious causative gene defect. A candidate locus for this syndrome was mapped to chromosomal region 2p14 by microcell-mediated chromosome transfer in two unrelated families. Unexpectedly, analysis of genes in this area identified mutations in two different genes, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
320
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(345 citation statements)
references
References 31 publications
23
320
2
Order By: Relevance
“…At least three instances of autosomal recessive disruption in genes playing an essential role in Fe-S biogenesis result in human phenotype accompanied by characteristic defects in complexes I, II and III of the mitochondrial respiratory chain. 14,15 In agreement with this, targeted disruption of fdx2 and NFU1, another late-acting maturation factor for a subset of mitochondrial Fe-S proteins, resulted in severely decreased content and activity of mitochondrial complex II (SDH) and the mitochondrial and cytosolic aconitases (only in fdx2 depletion) as well as impairment of lipoic acid containing enzymatic complexes. 16,17 Indeed, we also detected similar deficiencies in our Fdx2-deficient patient indicating that both SDH functional (enzyme activity) and content (immunoblotting) are affected (Figure 2).…”
Section: Discussionmentioning
confidence: 54%
“…At least three instances of autosomal recessive disruption in genes playing an essential role in Fe-S biogenesis result in human phenotype accompanied by characteristic defects in complexes I, II and III of the mitochondrial respiratory chain. 14,15 In agreement with this, targeted disruption of fdx2 and NFU1, another late-acting maturation factor for a subset of mitochondrial Fe-S proteins, resulted in severely decreased content and activity of mitochondrial complex II (SDH) and the mitochondrial and cytosolic aconitases (only in fdx2 depletion) as well as impairment of lipoic acid containing enzymatic complexes. 16,17 Indeed, we also detected similar deficiencies in our Fdx2-deficient patient indicating that both SDH functional (enzyme activity) and content (immunoblotting) are affected (Figure 2).…”
Section: Discussionmentioning
confidence: 54%
“…The function of these holo-heterodimers is still not clear (6,9,50,51). The only characterized physiological role for a GrxBolA holo-heterodimer is in sensing the intracellular iron/Fe-S cluster status in yeast.…”
Section: Rieske-type [2fe-2s] Coordination Occurs In Grx-bola_hmentioning
confidence: 99%
“…(Fig. 2) (12,13,(85)(86)(87)(88). Recent in vivo evidence indicates that the mitochondrial protein Nfu1 can interact with the [4Fe-4S] cluster machinery and with potential [4Fe-4S] target proteins, thus supporting its targeting function (89).…”
Section: Synthesis and Trafficking Of The [4fe-4s] Cluster In Mitochomentioning
confidence: 99%
“…Two recent in vivo studies in yeast and a BOLA3 patient analysis suggested that Bol3 and Bol1 are involved in the maturation of a sub-class of mitochondrial [4Fe-4S] proteins, especially succinate dehydrogenase and lipoic acid synthase with its two [4Fe-4S] clusters, whereas several [2Fe-2S] proteins were assembled independently of the Bol proteins (Fig. 2) (13,89,93). Like Nfu1, the mitochondrial Bol proteins are not essential for viability of S. cerevisiae, and residual maturation of their target proteins was observed even in BOL double null mutants.…”
Section: Synthesis and Trafficking Of The [4fe-4s] Cluster In Mitochomentioning
confidence: 99%